The Role of Social Capital on Consumer Behavior and Sustainability of Religious Business Units (Case Study of Waringin Store, Mataram City) - Siswoyo, Alfian; Wibowo, Joshi Maharani; Setyaningrum, Idfi (Gorontalo Development Review, 2024)
This research is aim to get a analyze social capital's impact on the sustainability of a business unit in the trade sector for ceremonial or religious activity products for Hindu communities. The data used is primary data obtained through in-depth interviews with a data triangulation method. The findings of the research indicate that there is a relationship between social capital and business sustainability, through Bourdieu's theory on how social capital can generate economic resources. The expression of socio-economic relationships is marked by activities in behaviors or actions that support social interaction, such as partnerships, activities characterized by networking participation, reciprocity (exchange or reciprocal activities between individuals or groups), trust, values, social norms, and proactive actions. The application of social capital in the case of Toko Waringin facilitates customers through access to a very strategic location, availability of products, and a variety of Hindu religious ceremonial supplies, with a good inventory system and flexible service times.